قضية رحمة الله في التفسير الصوفي الإشاري: The Mercy of Allah in Tafsīr as-Ṣūfī al-Ishārī - Hashim, Mahyuddin (Maʿālim al-Qurʾān wa al-Sunnah, 2019)
Some exegetes explained the Qur’anic verses about the mercy of Allah through ṣūfī al-ishārī (mystical allegorical allusion) interpretation which is one of the exegetical approaches to describe the meaning of the Qurʾān. This interpretation is based on hidden symbolic imagery contrary to the conventional interpretation of the Qurʾān. The purpose of this article is to extrapolate the concept of raḥmat Allāh (the mercy of Allah) in Quranic verses with reference to tafsīr ṣūfī al-ishārī. This research is based on the textual study by using content analysis method in criticism and evaluation. The paper opines that adopting tafsīr ṣūfī al-ishārī in the concept of the mercy of Allah is in agreement with the conditions of conventional tafsīr.